Comparative study on feeding of growth promoter (Aviator™) and enzymes (Acinor™) on growth performance of broiler (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The experiment was conducted to evaluate the effects of growth promoter (Aviator™) and enzymes (Acinor™) with basal feed. A total of 40 Cobb-500 Broiler day old chicks were reared in an open sided gable type house for a period of 5 weeks from 24th september to 28th october, 2017. Body weight and feed intake were recorded on day 0, 7, 14, 21, 28 and 35. The experiment was conducted in a Completely Randomized Design (CRD). Birds were randomly distributed into four dietary groups i.e control (T0) with basal diet, T1 with basal diet and growth promoter (GP) @ 2 gm/kg of feed; T2 with basal diet and enzymes (EZ) @ 0.4 gm/kg of feed and T3 with basal diet and GP plus EZ (2 gm/kg + 0.4 gm/kg). The records were kept on body weight, feed intake and mortality while weight gain, feed conversion ratio (FCR) and survivability were calculated. Broiler chicks that received GP and a combination of GP+EZ treatments showed significant improvement in performance (p